Study of Flow and Temperature Effect on Carbon Steel in Oil and Gas Environment - R., Daud; N. Zara, Kolan; Mas Ayu, Hassan; Siti Haryani, Tomadi; Sudin, Izman (2015)
The effect of flow rate and temperature are believed to contribute in corrosion rate of carbon steel with presence of CO2 in oil and gas environment. The aim of the study are to investigate the effect of temperature and fluid flow rate on corrosion rate which focus on the formation of protective layer (FeCO3) on carbon steel. In this experiment, the specimen used is carbon steel (AISI 1045) and it is grinded with sand paper of 180, 280 and 400 grit on the surface of carbon steel. The specimen was tested with 3.5% NaCl and pH 4 with different temperature of 250C, 500C and 800C. The fluid flow rate is varied by different rate of rotation which is 0 rpm, 500 rpm, 1000 rpm and 2000 rpm with the injection of saturated CO2. Linear Polarization Resistance (LPR) is used to measure the corrosion rate and the formation of protective layer is observed under Field Emission Scanning Electron Microscopy (FESEM) and Energy-dispersive X-ray Spectroscopy (EDX). The effect of flow rate and temperature seems influence the corrosion rate significantly. While the flow rate 2000 rpm shows the highest corrosion rate due to its turbulence pattern of the fluid flowing and enhanced the corrosion to occur. The scaling temperature obtain in this investigation is 500C since at this point the corrosion rate seems to be the highest. This is due to the formation of porous and non-protective FeCO3 layer on the wall of carbon steel. While, at 800C the corrosion rate drops due to the formation of a dense protective layer. It is can be concluded that the scaling temperature is occurred at 500C and started to decrease at 800C. This finding shows that corrosion at maximum rate will occur faster than reported by previous study which the maximum corrosion rate occurred only at above 600C.